Myth, Materiality, and Book of Mormon Apologetics: A Sacred Text and its Interpreters. Issue 3 (16th November 2017) - Hammer, Olav
Abstract : The Book of Mormon, first published in 1830, presents a detailed account of the migration of several groups from the ancient Near East to the Americas, and how these groups became the ancestors of the Native Americans. The description of these migrations fits well with common early nineteenth-century beliefs about the origins of the indigenous populations of America, but contradicts in numerous ways the scientific consensus that emerged roughly a century ago. Key apologists have constructed a range of arguments for the literal truth of the Book of Mormon account. This article examines the structure of a number of common apologetic arguments, and shows how interpretive commentary can project new meanings on a canonical text.